Investigation of the frequency and causes of injuries in football players - Akcan, Firat (Progress in Nutrition, 2021)
Study Objectives: Football, by its nature, is a sport in which physical struggle is very intense and in which related injuries can occur. It is thought that it may be useful to know what injuries occur in amateur football players and why they occur. The aim of this study is to investigate the frequency and causes of injuries seen in male athletes playing football in amateur sports clubs in Gaziantep. Methods: A total of 200 athletes from the super amateur league (n: 16), amateur (n: 45), U19 (n: 69), U17 (n: 16) and other leagues (n: 54) were included in the study on a voluntary basis. Survey model was used in this study. The Sports Injuries Questionnaire developed by Yıldız was applied to the athletes. A chi-square test was used to compare the participants' personal characteristics. Results: A statistically significant association (p